A Nelsonian Response to 'the Most Embarrassing of All Twelfth-century Arguments'. Issue 2 (2nd April 2020) - Estrada-González, Luis; Ramírez-Cámara, Elisángela
Abstract : Alberic of Paris put forward an argument, 'the most embarrassing of all twelfth-century arguments' according to Christopher Martin, which shows that the connexive principles contradict some other logical principles that have become deeply entrenched in our most widely accepted logical theories. Building upon some of Everett Nelson's ideas, we will show that the steps in Alberic of Paris' argument that should be rejected are precisely the ones that presuppose the validity of schemas that are nowadays taken as some of the most trivial logical truths: ( A ∧ B ) →AB A and ( A ∧ B ) →AB B, i.e. Simplification.